2021
DOI: 10.3390/children8121203
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies for Children and Parents Sharing Self-Management in Childhood Chronic or Long-Term Conditions: A Scoping Review

Abstract: Worldwide, the prevalence of chronic (or long-term) conditions in children and young people from birth to 18 years (children) is increasing. Promoting competent and effective self-management skills early in the trajectory is important to improve adherence to treatment and optimise quality of life. Successful self-management, therefore, requires parents and children who are developmentally able to develop a range of complex skills, including the use of digital technologies. This scoping review aimed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Not only PGs have expressed interest in receiving information via digital technologies in the past [31]. It was also shown that children display greater acceptance of medical treatment when using digital technologies [32]. Moreover, patients whose dental treatment included IOS reported higher comfort and less chairside time compared to conventional impression techniques [33].…”
Section: Discussionmentioning
confidence: 99%
“…Not only PGs have expressed interest in receiving information via digital technologies in the past [31]. It was also shown that children display greater acceptance of medical treatment when using digital technologies [32]. Moreover, patients whose dental treatment included IOS reported higher comfort and less chairside time compared to conventional impression techniques [33].…”
Section: Discussionmentioning
confidence: 99%
“…Providing psychological support using technology is well received within the young population 27 . A recent scoping review showed that technologies such as mobile apps and websites can assist the self‐management of LTCs, are an acceptable method of delivering information and can promote the development of effective self‐management skills by parents and children 28 . However, the authors have also identified the need for future technology design to include children and parents in all stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not just the transfer of care to an adult service, but equally importantly the gradual transfer of responsibility for the management of the condition from parents to adolescents, with the goal to ultimately becoming independent, autonomous young adults 11 . Poor transition leads to inadequate management of a chronic condition which is costly to the healthcare system as well as to the teenager's well‐being 12–15 . Accordingly, effective transition has been shown to improve both long‐term outcomes and the young persons' experience 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Poor transition leads to inadequate management of a chronic condition which is costly to the healthcare system as well as to the teenager's well-being. [12][13][14][15] Accordingly, effective transition has been shown to improve both long-term outcomes and the young persons' experience. [16][17][18] However, a systematic review by Khaleva et al 11 identified significant deficiencies in the current approach to the transition of young people with allergy and asthma.…”
mentioning
confidence: 99%